Comparison of soil treatment using natrium chloride and copper sulphate for electrical earthing system: article - Mohd Yusoff, Muhammad Aqib (UiTM, 2014)
This paper describes the comparison of soil treatment using natrium chloride and copper sulphate for electrical earthing system. Achieving good resistivity from the soil — some poor soils needs improvement in which to reduces its resistivity to make sure the grounding rods can conduct in such large electrical currents because these grounding rods always depends on the surrounding of the soil. The electrolytes like natrium chloride and copper sulphate seems to be a good material in which giving a lower resistance for the soil. The copper sulphate will gives lower resistivity to the soil compared to natrium chloride for better earthing.